Chemical prospection of moringa oil and bromatological quality of the pie from different types of grain processing (Research, Society and Development, 2020)
Moringa oleifera Lam. is a drought-resistant plant and able to survive in poor soils, obtaining up to three harvests per year. The objective of this work was to study the chemical prospecting of the oil and the bromatological quality of the moringa cake amog different temperatures of drying (40, 55, and 70 ºC) as well as from the oil chemical and mechanical extraction methods. The extracted oils were qualitatively evaluated for acidity, peroxide and iodine levels, as well as the chemical composition of fatty acids by gas chromatography, of samples dried at different drying air temperatures. The pies from mechanical extractions were evaluated for water content, ether extract, crude protein, ash and fibers in neutral detergent. The drying air temperatures of 40, 55, and 70 ºC significantly affected the physical-chemical quality of the oil and the moringa cake, with the best result being the samples from the dry grains at 40 °C. The composition of the main fatty acids was not altered according to the statistical method applied, these being oleic fatty acid (73.60 to 77.07%), erucic (5.65 to 6.67%) and palmitoleic (4.90 to 5.72%). The chemical extraction of oil, although more efficient than the mechanical one, presented higher levels of acidity and peroxide. The content of fibers in neutral detergent and crude protein of the pie decreased significantly for dried grains with drying air temperature above 40 °C.